2000
DOI: 10.4049/jimmunol.165.4.2149
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M Stimulates the Growth of Dermal Fibroblasts Via a Mitogen-Activated Protein Kinase-Dependent Pathway

Abstract: Oncostatin M (OSM), a member of the hemopoietic cytokine family, has been implicated in the process of fibrosis and dermal wound healing. As a part of an ongoing study of the mechanisms of fibrosis and dermal wound healing, we have investigated the mechanism of the growth regulation of dermal fibroblasts by OSM. OSM stimulates the mitogenesis of dermal fibroblasts in a dose-dependent manner. This effect was completely blocked by anti-OSM IgG, but not by anti-IL-6 IgG. Furthermore, OSM induction was abolished b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
52
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 49 publications
5
52
0
1
Order By: Relevance
“…The maximal e ect observed was at a concentration of 2 ng ml 71 . This mitogenic e ect is consistent with a recent study, which showed that OSM induced the proliferation of dermal ®broblasts (Ihn & Tamaki, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The maximal e ect observed was at a concentration of 2 ng ml 71 . This mitogenic e ect is consistent with a recent study, which showed that OSM induced the proliferation of dermal ®broblasts (Ihn & Tamaki, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Incubation of ®broblasts with PD98059 markedly diminished OSM-induced mitogenesis, strongly suggesting that OSM stimulates the proliferation of ®bro-blasts via a MAPK-dependent pathway. Similar ®ndings have recently been reported for dermal ®broblasts (Ihn & Tamaki, 2000). Bornfeldt et al (1997) recently demonstrated that the MAPK pathway can either mediate or inhibit cell proliferation, depending on the induction of down-stream events, most notably COX-2 meditated production of PGE 2 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These are the first data specifically implicating MAP kinases in the regulation of OSM secretion, although OSM itself is known to induce MAP kinase phosphorylation in target cells [39,40]. The ERK inhibitor used is well validated, and does not affect other intracellular protein kinases at concentrations of <50 lM [41].…”
Section: Discussionmentioning
confidence: 83%